Areca jokowi: A New Species of Betel Nut Palm (Arecaceae) from Western New Guinea - Heatubun, Charlie D. (Phytotaxa, 2016)
A new species of betel nut palm, Areca jokowi, is described and illustrated here. This is the third species of Areca to have been described recently from New Guinea that is closely related to the widespread, economically important species A. catechu, the cultivated betel nut palm. A discussion of its morphological characters, distribution, ecology, habitat, uses and conservation status is provided, as well as a new identification key for western New Guinean Areca.